2019
DOI: 10.3989/gya.0692181
|View full text |Cite
|
Sign up to set email alerts
|

Variations in oil, protein, fatty acids and vitamin E contents of pumpkin seeds under deficit irrigation

Abstract: In the present study, pumpkin (Cucurbita Pepo L.) was grown under water stress to determine its effects on the chemical composition of the seeds (i.e., oil, protein, fatty acids and vitamin E), in Kayseri, Turkey. Irrigation treatments were designed to supply different portions of depleted moisture within the efficient root zone of the plants (60 cm). The treatments were arranged as supplying 100% (I100), 80% (I80), 60% (I60), 40% (I40), 20% (I20) and 0% (I0) of depleted moisture through a drip irrigation syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Ermiş (2010) reported the highest protein values of pumpkin seeds in the literature as in the range of 30.77%–37.90% and that results are overlapped with our study. Kırnak et al (2019), Srbinoska et al (2012), Nyam et al (2009), Ardabili et al (2011), Meru et al (2018), Nawirska‐Olszanska et al (2013), Kim et al (2012) report lower protein rates from our study results. It has been observed that the protein ratios of pumpkin seeds are higher than other oil seeds.…”
Section: Resultssupporting
confidence: 43%
“…Ermiş (2010) reported the highest protein values of pumpkin seeds in the literature as in the range of 30.77%–37.90% and that results are overlapped with our study. Kırnak et al (2019), Srbinoska et al (2012), Nyam et al (2009), Ardabili et al (2011), Meru et al (2018), Nawirska‐Olszanska et al (2013), Kim et al (2012) report lower protein rates from our study results. It has been observed that the protein ratios of pumpkin seeds are higher than other oil seeds.…”
Section: Resultssupporting
confidence: 43%
“…These results highlight the effect of climatic conditions on the concentration of vitamin E of P. halepensis . Indeed, the impact of genetic and environmental factors on the content and composition of oils and vitamins extracted from several plant species has been previously shown [29–34] …”
Section: Resultsmentioning
confidence: 99%
“…The utilization of medicinal plants and plant-derived products for therapeutic purpose is rapidly increasing and gaining attention globally because they exhibit little or no safety concern and their biofriendliness compared to synthetic medications. Cucurbita pepo (Pumpkin), an economically and nutritionally important fruitbearing vegetable belonging to the family Cucurbitaceae, is a reservoir of variety of nutrients and bioactive compounds such as unsaturated fatty acids, micro and macro minerals, α and γ tocopherols, β-carotene, proteins (albumin and globulins), vitamins and phytosterols [10][11][12][13][14].…”
Section: Developmentmentioning
confidence: 99%